Effect of fruit canopy position, harvest maturity and storage duration on post-harvest mealiness development of ‘Forelle’ pears (Pyrus communis L.) - Cronje, Rudolph John (Stellenbosch : Stellenbosch University, 2019)
Thesis (MScAgric)--Stellenbosch University, 2019.